The development and application of biological models for evaluation of direct nose-to-brain drug delivery systems - Mistry, Alpesh (2009)
The olfactory neuroepithelium is the only part of the central nervous system that is exposed directly to the external environment. Therefore, it is the only non-invasive drug delivery route to the brain. Surface modification of PS nanoparticles with chitosan C-PS), polysorbate 80 (P80-PS) and polysorbate 80+FCS (P80-FCS-PS) changed the toxicity and distribution of these nanoparticles in olfactory mucosae. In addition, a reduction in nanoparticle diameter from 200nm to 20nm increased nanoparticle mucosal penetration and possibly also their cellular toxicity.